ENGLAND: DID THE DECISION OF THE SUPREME COURTIN THE CASE OF JONES V KERNOTT CLARIFY THE LAWIN RELATION TO TRUSTS OF THE FAMILY HOME? - Orawiec, Bartłomiej (Review of European and Comparative Law, 2017)
This dissertation will focus on common intention constructive trusts in relation to shared ownership of the family home predominantly in relation to unmarried couples. These trusts are particularly important because as opposed to married couples where the court may determine a couple’s financial and property issues upon divorce using the provisions of the Matrimonial Causes Act 1973, the position of unmarried couples is not covered by any legislation and so judges need to refer back to case law and property law in order to establish the equitable ownership of property.